Mulan II [videorecording (DVD)] - Ming-Na, 1963-; Moseley, Mark; Wong, B. D.; Kwan, Michelle, 1980-; Liu, Lucy, 1968-; Henry, Jillian; Tom, Lauren; Morita, Pat, 1932-2005; McNeely, Joel; Tesori, Jeanine (Disney DVD., 2005)
The magnificent legend of Mulan continues in an all-new movie. The courageous heroine is back, along with favorite characters and some new friends, including the mischievous Mushu, who wants to keep Mulan single so he can retain his job as her guardian.